Ventilatory chemoreflexes at rest following a brief period of heavy exercise in man. - Clement, I; Pandit, J; Bascom, D; Robbins, P (1996)
1. Ventilatory chemoreflex responses have been studied at rest during the recovery from a brief period of heavy exercise. 2. Six young, healthy male subjects each undertook four experimental studies. In each study measurements were made at rest during recovery from an exhaustive 1-2 min sprint on a bicycle ergometer with a workload of 400 W. Three levels of end-tidal O2 pressure (Po2) were employed. Continuous ventilatory measurements were made during euoxia (end-tidal Po2, 100 Torr), hypoxia (end-tidal Po2, 50 Torr) and hyperoxia (end-tidal Po2, 300 Torr). Arterialized venous blood samples were drawn during each of the measurement periods for the estimation of arterial pH. In two of the studies, end-tidal CO2 pressure (Pco2) was maintained throughout at 1-2 Torr above the eucapnic level that existed prior to exercise (isocapnic post-exercise protocol, IPE). In the other two studies, end-tidal Pco2 was allowed to vary (poikilocapnic post-exercise protocol, PPE). Data from a previously published study on the same subjects involving an infusion of hydrochloric acid were used to provide control data with a varying level of metabolic acidosis, but with no prior exercise. 3. Ventilation-pH slopes in the IPE protocol were no different from control. Ventilation-pH slopes in the PPE protocol were significantly lower than in the IPE and control protocols (P < 0.05, ANOVA). This difference may be due to the progressive change in end-tidal Pco2 in the PPE protocol compared with the constant end-tidal Pco2 in the IPE and control protocols. 4. An arterial pH value of 7.35 was attained 30.4 +/- 2.7 min (mean +/- S.E.M.) after the end of exercise in the IPE protocol and 17.1 +/- 1.4 min after the end of exercise in the PPE protocol. 5. Hypoxic sensitivities at an arterial pH of 7.35 were not significantly different between the IPE, PPE and control protocols (ANOVA). 6. Euoxic ventilation at an arterial pH 7.35 was significantly greater than control for the IPE protocol (P < 0.001, Student's paired t test) and no different from control for the PPE protocol. 7. The results suggest that 30 min after heavy exercise, ventilation remains stimulated by processes other than the post-exercise metabolic acidosis, and that changes in peripheral chemoreflex sensitivity to hypoxia and acid are not implicated in this.